2018
DOI: 10.1371/journal.pone.0195996
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity measured with wrist and ankle accelerometers: Age, gender, and BMI effects

Abstract: Physical activity (PA) is associated with various aspects of physical and mental health and varies by age and BMI. We aimed to compare PA measures obtained with wrist and ankle accelerometers and characterize their associations with age and BMI. We assessed PA mean and PA variability (indexed by coefficient of variation (CV)) at daytime and nighttime periods for seven consecutive days (M = 152.90 h) in 47 healthy participants (18–73 years old, 21 females). Diurnally, mean PA for both ankle and wrist and CV of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…This is the first study reporting significant association of accelerometer-determined MVPA with NC of nationally representative samples from urban populations from LA countries (Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela). This study supports previous research that has shown negative relationships between accelerometer-determined MVPA and body composition variables [61, 62]. Our results corroborate those of Van Dyck et al [62], who reported significant associations of accelerometer-determined MVPA with BMI in adults from 12 countries, independent of country and SEL.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first study reporting significant association of accelerometer-determined MVPA with NC of nationally representative samples from urban populations from LA countries (Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela). This study supports previous research that has shown negative relationships between accelerometer-determined MVPA and body composition variables [61, 62]. Our results corroborate those of Van Dyck et al [62], who reported significant associations of accelerometer-determined MVPA with BMI in adults from 12 countries, independent of country and SEL.…”
Section: Discussionsupporting
confidence: 93%
“…Because women were less physically active than men on actigraphy, we decided to also look at predictor relationships by sex, particularly in light of the NIH recommendation to do so in biomedical research [16]. Less activity in women was not an anticipated finding as several epidemology studies have not observed significant sex differences in the general population [8, 11, 22]; however, the women in our study were about 10 years older than the men, largely due to the number of enrolled young men with testicular cancer, and activity level does gradually decrease with age. Assessing activity level after the cancer diagnosis conveys current levels, but it does not indicate to what degree the activity level is a function of disease status.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work, a lower amplitude, lower mesor, earlier acrophase, and more fragmented rhythm have been described in older adults [6, 9, 15•, 16, 17]. Daytime activity levels are also lower at old age [18], but nighttime activity levels do not necessarily change in old age [19]. The stability of the 24-h activity rhythm seems to remain similar across ages [16], and has even been suggested to be higher in old age [20].…”
Section: -H Activity Rhythms and Agingmentioning
confidence: 97%